Значення гену PCSK9 в порушенні метаболізму ліпідів та лікуванні гіперхолестеролемії - Панчишин, Ю.М. (Медична гідрологія та реабілітація, 2011)
Proprotein convertase subtilisin/kexin type 9 (PCSK9) is a key regulator of circulating levels of lowdensity lipoprotein (LDL) particles. PCSK9 acts mainly by enhancing degradation of the LDL receptor in the liver. Several gain-of-function and loss-of-function mutations in the PCSK9 gene have been identified and linked to hypercholesterolemia and hypocholesterolemia. PCSK9 inhibition represents a very promising target for reducing LDL-C levels and decreasing the risk of atherosclerotic cardiovascular diseases, but human clinical trials will be crucial to assess the potency and safety of PCSK9 inhibitors.